Energy, Vibration, Consciousness, Universe, Cosmos & Almighty God! (Journal of Politics and International Studies, 2025)
Although the ignorant humanity stands today perpetually at the frontier of understanding energy and vibration on the one hand and mind and soul on the other altogether facing the vastness of the cosmos with awe and inquiry, yet the time-space configuration on and around earth work as a covering whereupon the universe is painted with boundless dimensions, thereby raising few profound questions as regards their true credentials. If this configuration has no perceived limits for the human beings, their effort to comprehend the unknown mysteries often turns into a deep intellectual thinking or philosophical exercise. In fact, the time and space configuration mark as factual or real phenomena which demarcate the duration of living bodies and the mass and expanse of matter, thus forming the spirit of consciousness and its realisation. Further in its quest to understand the infinite universe or multiverse or cosmos, the humanity scuffle with the foundational and limitless ideas of the time-space configuration and the Almighty God as the Supreme Divine or the Highest Authority. Although still an unanswered mystery before the humans underway to unravel the crux of the supreme authority, yet a day may possibly come when the divinity shall not remain an enigma before the wandering masses.